Analyzing Validity and Reliability Instruments of Teacher Made Test for English Subject - Nida Mahdiana Zahiroh; Imam Ghozali; Moh. Arif Mahbub (Linguapedia, 2017)
The development of education world not only supported by the factors of teaching such as teaching methods, learning process and others but also influenced by the factors which doesn’t related with the teaching process at the class that is evaluation of learning. The writer conducted observation in Eight grade at MTs Bustanul Ulum Kasiyan Timur. The objectives of this research are to describe the characteristics of the item of teacher made test for English subject for Eight grade in MTs Bustanul Ulum Kasiyan Timur – Puger in the 2014/2015 Academic Year on daily test 1, daily test 2 and daily test 3 which are include validity and reliability. Type of this research is descriptive research with analyzing the item of question, reviewed from its content validity based on the syllabus and reviewed from theirs face and construct validity based on the question made by teacher an reviewed its criterion-related validity based on the answer of the students at MTs Bustanul Ulum. Based on the data analysis which is done, so it can be concluded that on generally the item of the teacher made test on daily test 1, 2 and 3 has not fulfill the criteria of content validity. From face validity on daily tests 1, 2 and 3 the teacher using layout well. On construct validity, the teacher using different skill to make the question between daily test 1, 2 and 3. And from Criterion-related validity on daily tests 1, 2 and 3 has not fulfill standard of KKM. And for reliability has not reliable because on daily test 2 and 3 have low reliability.